Study of kefir drinks produced by backslopping method using kefir grains from Bosnia and Herzegovina: Microbial dynamics and volatilome profile. (November 2020) - Garofalo, Cristiana; Ferrocino, Ilario; Reale, Anna; Sabbatini, Riccardo; Milanović, Vesna; Alkić-Subašić, Mersiha; Boscaino, Floriana; Aquilanti, Lucia; Pasquini, Marina; Trombetta, Maria Federica; Tavoletti, Stefano; Coppola, Raffaele; et al.
Graphical abstract: Highlights: The microbial dynamics and volatilome profile in kefir production have been studied. A microbial shift was observed during the production of backslopped kefir. Backslopped kefir samples showed higher pH, protein, lactose and ash content. Backslopped kefir was correlated with cheesy, buttery, floral and fermented odors. This is the first report on volatilome profile of the backslopped kefir. Abstract: Kefir is a well-known health-promoting beverage that can be produced by using kefir grains (traditional method) or by using natural starter cultures from kefir (backslopping method). The aim of this study was to elucidate the microbial dynamics and volatilome profile occurring during kefir production through traditional and backslopping methods by using five kefir grains that were collected in Bosnia and Herzegovina. The results from conventional pour plating techniques and amplicon-based sequencing were combined. The kefir drinks have also been characterized in terms of their physico-chemical and colorimetric parameters. A bacterial shift from Lactobacillus kefiranofaciens to Acetobacter syzygii, Lactococcus lactis and Leuconostoc pseudomesenteroides from kefir grains in traditional kefir to backslopped kefir was generally observed. Despite some differences within samples, the dominant mycobiota of backslopped kefir samples remained quite similar to that of the kefir grain samples. However, unlike the lactic acid and acetic acid bacteria, the yeast counts decreased progressively from the grains to the backslopped kefir. The backslopped kefir samples showed higher protein, lactose and ash content and lower ethanol content compared to traditional kefir samples, coupled with optimal pH values that contribute to a pleasant sensory profile. Concerning the volatilome, backslopped kefir samples were correlated with cheesy, buttery, floral and fermented odors, whereas the traditional kefir samples were correlated with alcoholic, fruity, fatty and acid odors. Overall, the data obtained in the present study provided evidence that different kefir production methods (traditional vs backslopping) affect the quality characteristics of the final product. Hence, the functional traits of backslopped kefir should be further investigated in order to verify the suitability of a potential scale-up methodology for backslopping.